Ocorrência de contusões em carcaças bovinas em frigorífico - Petroni, Rudge; Bürger, Karina Paes [UNESP]; Gonçalez, Patrícia Oliveira; Marques, Rossi Gabriel Augusto [UNESP]; Vidal-martins, Ana Maria Centola; Aguilar, Carlos Eduardo Gamero [UNESP] (Universidade Federal da Bahia (UFBA), 2013)
The animal welfare is a series of practices that involves the maintenance of psychological and physiological freedoms of animals, to them remain healthy until slaughter and provide a satisfactory quality carcass and to avoid unnecessary suffering to animals. One way to evaluate the animal welfare is monitoring the occurrence of bruises on carcasses that is an indicative of inadequate management of the animals. The present study aimed to evaluate the occurrence of bruises in cattle carcasses at a slaughterhouse located in the Midwest Region of the State of São Paulo, Brazil. Was applied a check-list that determined the presence of bruises, the location and severity of them, ranking among scores I to III. Was observed in 98% (880/898) of the animals the presence of contusion. The Grade I injuries in the region of the hips at half carcasses had higher incidence with an average of 61.8% between the right and left sides. Could be observed multiple lesions in several animals slaughtered. In 133 animals observed were removed 15.6 kilograms of material only the injured region only of the hips, demonstrating economic losses to cattle farmers and industries for failures in animal welfare practices. The inappropriate pre-slaughter management compromises animal welfare and the quality of carcasses, discrediting our products on international meat trade and consisting in economic losses to the national cattle herds.

O bem-estar animal é uma prática que implica na manutenção das liberdades psicológicas e fisiológicas dos animais, para que seus organismos permaneçam saudáveis até o abate, proporcionando uma carcaça com qualidade e evitando sofrimentos desnecessários aos mesmos. Uma forma de avaliar o bem-estar é através da monitoração da ocorrência de contusões nas carcaças, um indicativo de manejo inadequado dos mesmos. Objetivou-se avaliar a ocorrência de contusões em carcaças bovinas em um matadouro-frigorífico localizado na Região Centro-oeste do Estado de São Paulo. Assim, foi aplicada check-list, para determinação da presença de contusões, o local e a gravidade das mesmas, classificando-as entre escore I a III. Do total de animais avaliados, 98% (880/898) apresentaram contusão. As contusões de grau I na região do coxão das meias carcaças tiveram maior incidência com média de 61,8% entre os lados direito e esquerdo. Também foram observadas múltiplas lesões em diversos animais abatidos. Em 133 animais avaliados foram retirados 15,6 kg de material lesionado na região do coxão apenas, demonstrando grandes prejuízos econômicos aos produtores e às indústrias por falhas em bem-estar animal. O manejo pré-abate inadequado compromete o bem-estar animal e a qualidade das carcaças, desprestigiando nossos produtos no comércio internacional da carne bovina e consistindo em perdas econômicas à pecuária bovina nacional.
Bruises occurrence in cattle carcasses at a slaughterhouse
Keywords: Animal welfare; Lesions; Meat quality; Slaughter; abate; Bem-estar animal; lesões; qualidade de carne